Discovery of diazepane amide DORAs and 2-SORAs enabled by exploration of isosteric quinazoline replacements. Issue 21 (1st November 2015) - Roecker, Anthony J.; Mercer, Swati P.; Bergman, Jeffrey M.; Gilbert, Kevin F.; Kuduk, Scott D.; Harrell, C. Meacham; Garson, Susan L.; Fox, Steven V.; Gotter, Anthony L.; Tannenbaum, Pamela L.; Prueksaritanont, Thomayant; Cabalu, Tamara D.; et al.
Graphical abstract: Abstract: Dual orexin receptor antagonists (DORAs), or orexin 1 (OX1 ) and orexin 2 (OX2 ) receptor antagonists, have demonstrated clinical utility for the treatment of insomnia. Medicinal chemistry efforts focused on the reduction of bioactivation potential of diazepane amide1 through the modification of the Western heterocycle resulted in the discovery of suvorexant, a DORA recently approved by the FDA for the treatment of insomnia. A second strategy towards reducing bioactivation risk is presented herein through the exploration of monocyclic quinazoline isosteres, namely substituted pyrimidines. These studies afforded potent DORAs with significantly reduced bioactivation risk and efficacy in rodent sleep models. Surprisingly, side products from the chemistry used to produce these DORAs yielded isomeric pyrimidine-containing diazepane amides possessing selective OX2 R antagonist (2-SORA) profiles. Additional exploration of these isomeric pyrimidines uncovered potent 2-SORA diazepane amides with sleep efficacy in mouse EEG studies.